PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA KARYAWAN DI PT. WIKA INDUSTRI ENERGI TBK - Sandi Sandi; Muhammad Yusuf Maulana (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
Human resources are the most important factor in an organization or company. Human resources are associated with how people work and are managed in the organization. Human resources are a valuable resource, human resources will run effectively when developed and driven by a consistent policy that encourages the emergence of commitments, consequently the willingness of employees will evolve to act more flexibly in adapting to the interests of the Organization to achieve excellence, The type of research used is Research survey with Metode Research in the form of data collection using questionnaires. Sample selection is done by Sampling saturation. Sample of 33 respondents. The data Analysis Model used is a double linear regression analysis Regression Test results show that 76.8% of performance factors can be explained by leadership Styles, work motivation and organizational culture while the rest is 23.2% influenced by other variables not examined in this study. While the test results F showed that the simultaneous variables of the leadership style, work motivation and organizational culture by sImultan Significant effect on the employee 's performance with the analysis result is the value Fcount (36,230)> FTable (2,92). T test result indicates that the leadership style variables Show the results of the TCount analysis (3.152) where Ttable (1.699) then a partial Variabel Style leadership is significant to the employee's performance at PT. Wika Industri Energi Tbk.